2013
DOI: 10.1177/0892705713503850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cross-linked system on morphology and properties of thermoplastic vulcanizates based on isotactic polypropylene and ethylene propylene diene monomer

Abstract: Thermoplastic vulcanizates (TPVs) based on isotactic polypropylene (iPP) and oil-free/ oil-extended ethylene propylene diene monomer (EPDM) rubber were prepared by dynamic vulcanization. Their rheological and tensile properties as well as morphological peculiarities were examined and compared with those of uncured blends. Vulcanization was performed using two types of cross-linking agents: phenolic resin and sulfuraccelerating systems. Dynamic vulcanization was shown to change the melt viscosity of oil-free an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[ 26‐29 ] The sulfur curing system was selected in this work to achieve better co‐crosslinking network and get better comprehensive properties. [ 30‐35 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 26‐29 ] The sulfur curing system was selected in this work to achieve better co‐crosslinking network and get better comprehensive properties. [ 30‐35 ]…”
Section: Introductionmentioning
confidence: 99%
“…Due to these unique characteristics, TPEs show great importance in applications such as automotive, electrical cable, and construction. [17][18][19][20][21] Nowadays, the usage of waste ground rubber tire (WGRT) has attracted great attention because of increasing number of vehicles. 22,23 Van Beukering and Janssen 24 reported that about 800 million tires were discarded all over the world every year, which was estimated to increase by 2% annually; and Sienkiewicz et al reported that approximately 1.4 billion unit tires were produced around the globe every year.…”
Section: Introductionmentioning
confidence: 99%